Scientific production on surgical nursing: analysis of the quantitative studies carried out between 2005 and 2009 - Keila Maria de Azevedo Ponte; Maria Cristina Leite Araújo Borges; Francisca Adriana Barreto; Thereza Maria Magalhães Moreira; Lúcia de Fátima da Silva; Ana Virgínia de Melo Fialho (Universidade Federal do Ceará, 2012)
This study aimed to analyze the characteristics of quantitative studies of nursing scientific publication in the surgical area. Research with quantitative approach carried out in the Virtual Healthcare Library with articles of quantitative nature, published from 2005 to 2009, in journals classified as A1, A2 and B1 by the Capes Nursing Qualis system 2008, full-text available on-line and in Portuguese. 28 articles were analyzed and it was detected that most of them are descriptive, exploratory, cross-sectional and retrospective. The most adopted instrument of data collection was the form; as disposition of data analysis, the use of tables and of simple and relative frequency; as database, the Excel program; and as statistical tests, the chi-square and Fisher. Researches with quantitative approach in surgical nursing area have been published in journals of national impact with the main characteristics of this type of approach.